2002
DOI: 10.1182/blood.v99.8.2740
|View full text |Cite
|
Sign up to set email alerts
|

Receptor tyrosine kinase, EphB4 (HTK), accelerates differentiation of select human hematopoietic cells

Abstract: EphB4 (HTK) and its ligand, ephrinB2, are critical for angiogenesis and result in fatal abnormalities of capillary formation in null mice. EphB4 was originally identified in human bone marrow CD34 ؉ cells by us and has since been reported to be expressed in erythroid progenitors, whereas the ligand ephrinB2 is expressed in bone marrow stromal cells. Reasoning that the developmental relationship between angiogenesis and hematopoiesis implies common regulatory molecules, we assessed whether EphB4 signaling influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…We previously noted that overexpression (activation) of EphB4 led to accelerated exit of primitive adult hematopoietic cells from a functional stem cell population. 29 In the setting of the EphB4-deficient ES model used here, inhibition of differentiation and preservation of a primitive cell type was observed. Therefore the relative gradient of ligand/receptor expression and interaction may dictate the relative abundance of cells from specific differentiation stages.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We previously noted that overexpression (activation) of EphB4 led to accelerated exit of primitive adult hematopoietic cells from a functional stem cell population. 29 In the setting of the EphB4-deficient ES model used here, inhibition of differentiation and preservation of a primitive cell type was observed. Therefore the relative gradient of ligand/receptor expression and interaction may dictate the relative abundance of cells from specific differentiation stages.…”
Section: Discussionmentioning
confidence: 88%
“…Our previous studies indicated that EphB4 participates in adult hematopoiesis with primitive human CD34 ϩ hematopoietic cells undergoing accelerated differentiation in the context of activated EphB4. 29 We therefore examined EphB4 effects on the hemangioblast, where the processes of hematopoiesis and vasculogenesis intersect.…”
Section: Introductionmentioning
confidence: 99%
“…EPHB4 is expressed in hematopoietic progenitor cells and is downregulated during differentiation to mature erythroid cells upon removal of its ligand. 34 Active EphB4 enforces preferentially megakaryocytic and erythroid differentiation. It was described that the ephrinB2/EphB4 axis is dysregulated in multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have important implications for understanding and treating cancer because Eph proteins probably regulate angiogenic processes associated with tumor growth (Brantley et al, 2002;Dodelet and Pasquale, 2000;Ogawa et al, 2000;Pandey et al, 1995). Interestingly, EphB4 and ephrin-B2 also play a role in erythropoiesis by influencing hematopoietic cell lineages that share a common ancestry with endothelial cells (Suenobu et al, 2002;Wang et al, 2002b). Furthermore, Eph proteins play a role in platelet clustering and hence may be important for blood clotting at sites of vascular injury (Prevost et al, 2002).…”
Section: Functional Versatility Of Eph Proteinsmentioning
confidence: 99%